Medidas assecuratórias da efetividade da tutela jurisdicional da probidade administrativa - Almeida, Marcelo Eugênio Feitosa (2010)
This research refers some measures that provide and ensure effectiveness of legal protection of Administrative probity, considering the proceeding as an instrument of effective judicial protection, preveting a failing legislation, in other words, a leather standards merely symbolic. Among technical procedures expressly in Improbity Administrative Law(No. 8429 of 2 June 199), for example: the unavailability of goods (Article 7); asset forfeiture (Art 16 °) and removal of the agent the exercise of public office, employment or function (Article 20, paragraph), we intend to demonstrate others tools and techniques appropriated, that associated with the interpretations that give maximum effectiveness for our System of Rules, that seeks effectiveness a real protection of the Principle of Administrative Morality